Spiritual and moral education of students specialty "Physical education and sport" as a guarantee of forming a professional responsibility future specialist - Romanovskyi, Oleksandr; Zinchenko, Lina (Scientific Center of Innovative Researches OÜ, 2021)
Today in Ukrainian education there is a big gap in the education of spirituality and morality of future specialists, so that we are in a state of deep spiritual and moral crisis. The purpose of the article is to explore the elements of spiritual and moral education necessary for the formation of professional responsibility among students studying in the specialty "physical culture and sports". The research was based on comparative method, analytical study method and theoretical generalization of existing scientific concepts method. The article pays great attention to the elements of spiritual and moral education necessary for the formation of professional responsibility of students of the specialty "physical culture and sports". The importance of spiritual and moral-as an important source of professional responsibility of future specialists in physical culture and sports hasbeen revealed. Teachers have opportunities to educate students about spiritual and moral qualities, traits, positions, beliefs, values, sensations and other positive virtues. And do not forget about the teacher's own example, he must have high spiritual and moral values, be professionally responsible, sincere and competent, love his business and people.
Keywords: spiritual and moral education; professional responsibility; physical culture and sports; future specialists; values; spiritual education; moral education; samping; institution of higher education